Transformation of the failure state for the clinched joints of dissimilar materials using an auxiliary layer. (April 2023) - Gao, Xiaolei; Chen, Chao
Highlights: Auxiliary layer can effectively eliminate neck cracks in dissimilar material joints; The joints with auxiliary layer have an extremely outstanding static strength; Auxiliary layer is effective under different processes and different joining forces; Analysis for the failure mechanism of the joints with auxiliary layer. Abstract: Clinched joints of dissimilar materials are prone to cracks in the neck during the forming process. A new method by introducing an auxiliary layer is used to eliminate defects in the neck of the clinched joint. In this paper, auxiliary layers were added to the HC340LA/AL5052 and AL6061/AL5052 joints to investigate their contribution to joint joinability. The geometric characteristics, mechanical features, failure mechanism, and fracture morphology of the joint were also analyzed. The results show that the auxiliary layer can reduce the stress concentration in the joint neck, thus eliminating the defects in the joint neck. And this effect is demonstrated in different clinching processes. Additionally, the joints with auxiliary layers have remarkable joint strength. Among them, HC340LA/AL5052 joints with an auxiliary layer can reach the highest strength of 6877 N. In comparison to the conventional round joint with auxiliary layer, the square joint with auxiliary layer exhibit higher joining strength.